Association of serum transaminases with short- and long-term outcomes in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention. Issue 1 (December 2017) - Gao, Ming; Cheng, Yi; Zheng, Yang; Zhang, Weihua; Wang, Lin; Qin, Ling
Abstract Background Alanine transaminase (ALT) and aspartate aminotransferase (AST) are referred to as liver transaminases. Although used routinely in clinical practice for decades, their role as predictors of mortality has not been examined until recently. We studied the predictive value of these serum transaminases in patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI). Methods We analyzed records of 2417 consecutive STEMI patients with no preexisting liver disease who were treated with primary PCI at the Cardiovascular Center in the First Hospital of Jilin University. The outcomes measured were all-cause mortality at the first month and at 2 years. The relationship between the baseline serum transaminase levels and primary outcome was determined. Results We found a significant correlation between elevated liver transaminases and the Killip classification (P < 0.001 for ALT;P < 0.001 for AST), cardiac troponin I (P = 0.002 for ALT;P < 0.001 for AST), infarct-related coronary artery (P = 0.036 for ALT;P = 0.011 for AST), and pre-thrombolysis-in-myocardial-infarction (pre-TIMI) flow (P < 0.001 for ALT and AST). The serum level of ALT and AST were high along with the increasing of the grade of Killip classification. The primary infarct-related coronary artery in patients with ALT ≥95th percentage was left anterior descending artery (56%), followed by right coronary artery (36%). The OR for all-cause mortality at 2 years for participants with ALT ≥95th percentage was 5.370 (95% CI: 2.899–9.948), 7.034 (95% CI: 3.718–13.307) after adjustment for age and gender and 1.051 (95% CI: 0.302–3.652) after adjustment for all covariables. The OR for all-cause mortality at 2 years for participants with AST ≥95th percentage was 5.370 (95% CI 2.899–9.948) and 5.699 (95% CI 3.030–10.718) after adjustment for age and gender and 1.796 (95% CI: 0.588–5.481) after adjustment for all covariables. ALT (HR 1.004, 95% CI 1.001–1.006, P = 0.010) and AST (HR 0.999, 95% CI 0.998–1.000, P = 0.030) were associated with early all-cause mortality in patients with STEMI treated with PCI but not at 2 years post-procedure, unless for AST and ALT levels ≥95th percentage. Moreover, short- and long-term outcomes were significantly worse when both AST and ALT levels ≥95th percentage (P < 0.001). Conclusions Serum transaminases ≥95th percentage were associated with a significantly increased incidence of short- and long-term all-cause mortality. Trial registration Registration number:ChiCTR-EPC-16008199, 31 March 2016.